2013
DOI: 10.1002/rcm.6758
|View full text |Cite
|
Sign up to set email alerts
|

Structural identification of imatinib cyanide adducts by mass spectrometry and elucidation of bioactivation pathway

Abstract: Chemical structures of seven cyanide adducts of imatinib have been identified or proposed based on high-resolution MS/MS data. Mechanisms for the formation of the conjugates were also proposed. The findings may help to understand the mechanism of hepatotoxicity of imatinib in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…Though KCN is not a common trapping agent for soft electrophiles, its formation was proposed to occur through dehydration of hydroxymethyl derivative 27 to a p ‐imine‐methide RM 28 (Figure ). Otherwise, this soft electrophile did not lead to a GSH adduct, presumably because of steric hindrance issues . These results are in accordance with those of Kenny et al who also evidenced cyanide but not GSH adducts.…”
Section: Tki Metabolic Activation: Evidence Of Rm Formationsupporting
confidence: 92%
See 1 more Smart Citation
“…Though KCN is not a common trapping agent for soft electrophiles, its formation was proposed to occur through dehydration of hydroxymethyl derivative 27 to a p ‐imine‐methide RM 28 (Figure ). Otherwise, this soft electrophile did not lead to a GSH adduct, presumably because of steric hindrance issues . These results are in accordance with those of Kenny et al who also evidenced cyanide but not GSH adducts.…”
Section: Tki Metabolic Activation: Evidence Of Rm Formationsupporting
confidence: 92%
“…The hydroxylation of the methyl group on the p ‐toluidine moiety has been described in many reports . A cyanide adduct 29 was evidenced . Though KCN is not a common trapping agent for soft electrophiles, its formation was proposed to occur through dehydration of hydroxymethyl derivative 27 to a p ‐imine‐methide RM 28 (Figure ).…”
Section: Tki Metabolic Activation: Evidence Of Rm Formationmentioning
confidence: 84%
“…More recently, Zhao et al described a novel bioactivation pathway of erlotinib mediated by CYP3A4 and CYP3A5 to form a reactive ketene intermediate, which was trapped as an adduct with 4-bromobenzylamine [31]. In addition to these tyrosine kinase inhibitors, imatinib [20], axitinib [21], ponatinib [22], and sunitinib [23], have been shown to undergo bioactivation to form reactive metabolites, which were trapped as stable adducts. Recent findings regarding the bioactivation mechanisms of these tyrosine kinase inhibitors will be discussed below.…”
Section: Bioactivation Of Small Molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…In the study by Kenny et al, seven cyanide conjugates and one methoxylamine conjugate were observed from liver microsomal incubations in vitro [26]. Li et al, characterized the bioactivation of imatinib at the piperizine ring to form imine and imine–carbonyl (α,β-unsaturated) intermediates, and bioactivation of the p -toluidine moiety to form imine–methide intermediates trapped as cyanide adducts [20]. …”
Section: Bioactivation Of Small Molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation